Magnetic properties study of the anti-perovskite Mn3CuN compound by Monte Carlo simulations. (March 2019) - Khalladi, R.; Labrim, H.; Idrissi, S.; Mtougui, S.; Housni, I. El; Ziti, S.; Mekkaoui, N. El; Bahmad, L.
Abstract: In this paper, we investigated the magnetic properties of the cubic anti-perovskite Mn3 CuN compound by applying the Monte Carlo simulation (MCs). The magnetism in this metallic Mn3 CuN is provided by the Mn atoms (Mn 4+ )having the magnetic moment S = 1 and Cu (Cu 2+ ) atoms described by the magnetic spin momentσ = 1/2. However, we presented and discussed the ground state phase diagrams where we observed the stable phases in different planes corresponding to different physical parameters of the system at zero absolute temperature T = 0 K. On the other hand, a model describing the system is proposed to solve the Hamiltonian governing the system. The results of the physical parameters such as the susceptibilities, magnetizations and the specific heat behaviors are deduced for the finite size, as a function of temperature. Moreover, the thermal behavior of the previous physical quantities with the variation of the exchange coupling interactions, the crystal field and the external magnetic field are presented and discussed. Also, the curves of the magnetizations as a function of the crystal field are plotted. Finally, the magnetic hysteresis loops of the studied system have been drawn. Highlights: We study the Anti-perovskite Metallic compound Mn3 CuN. We performed Monte Carlo simulations to investigate this model. We outlined the exchange coupling interaction effect on the compensation temperature. The magnetic properties of such system are presented and discussed. The hysteresis loops are obtained and presented.